2017
DOI: 10.1016/j.nicl.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical thalamocortical connectivity is associated with response to vagus nerve stimulation in children with intractable epilepsy

Abstract: Although chronic vagus nerve stimulation (VNS) is an established treatment for medically-intractable childhood epilepsy, there is considerable heterogeneity in seizure response and little data are available to pre-operatively identify patients who may benefit from treatment. Since the therapeutic effect of VNS may be mediated by afferent projections to the thalamus, we tested the hypothesis that intrinsic thalamocortical connectivity is associated with seizure response following chronic VNS in children with ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 47 publications
8
89
0
Order By: Relevance
“…Thalamic nuclei form an integral component of the VagAN, receiving input directly from the NTS and PBN. 18 Our finding of more robust white matter microarchitecture in thalamocortical circuitry in VNS responders, particularly within the anterior and retrolenticular limbs of the internal capsule, anterior, superior, and posterior corona radiata, and posterior thalamic radiation, are therefore consistent with the known mechanism of action of VNS. 51 In a hypothesis-driven manner, we have previously shown that presurgical thalamocortical connectivity in resting-state fMRI is strongly associated with treatment response.…”
Section: Thalamocortical Circuitrysupporting
confidence: 80%
See 2 more Smart Citations
“…Thalamic nuclei form an integral component of the VagAN, receiving input directly from the NTS and PBN. 18 Our finding of more robust white matter microarchitecture in thalamocortical circuitry in VNS responders, particularly within the anterior and retrolenticular limbs of the internal capsule, anterior, superior, and posterior corona radiata, and posterior thalamic radiation, are therefore consistent with the known mechanism of action of VNS. 51 In a hypothesis-driven manner, we have previously shown that presurgical thalamocortical connectivity in resting-state fMRI is strongly associated with treatment response.…”
Section: Thalamocortical Circuitrysupporting
confidence: 80%
“…14 Although the exact mechanism of seizure reduction remains unclear, this vagus afferent network (VagAN) is thought to be the neural substrate of VNS efficacy. 18 In other conditions, brain connectomic profiling has been successfully used to predict poststroke motor recovery and response to psychiatric pharmacotherapy. 16,17 Recently, we described patterns of intrinsic connectivity within the thalamocortical components of the VagAN associated with treatment responsiveness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a neural network classifier examining DTI‐based structural connectomes from 50 TLE patients yielded a positive predictive value of 88% and negative predictive value of 79% in predicting Engel I outcomes, comparing favorably to a discriminant function classifier using only clinical variables . Measures of thalamocortical connectivity on resting‐state fMRI have similarly been used to predict favorable response (>50% seizure reduction) to vagus nerve stimulation, achieving an AUC of 86% using an SVM classifier in 21 pediatric patients . Antony et al, in contrast, applied an SVM classifier to measures of functional connectivity from stereo‐EEG in 23 patients undergoing anterior temporal lobectomy, achieving a sensitivity of 90% and specificity of 85% in predicting seizure freedom at 1 year of follow‐up .…”
Section: Applications In Surgical Management Of Epilepsymentioning
confidence: 99%
“…79 Measures of thalamocortical connectivity on resting-state fMRI have similarly been used to predict favorable response (>50% seizure reduction) to vagus nerve stimulation, achieving an AUC of 86% using an SVM classifier in 21 pediatric patients. 80 Antony et al, in contrast, applied an SVM classifier to measures of functional connectivity from stereo-EEG in 23 patients undergoing anterior temporal lobectomy, achieving a sensitivity of 90% and specificity of 85% in predicting seizure freedom at 1 year of follow-up. 81 Tomlinson et al also examined functional connectivity using interictal intracranial EEG recordings from 17 pediatric patients, achieving 100% sensitivity and 87.5% specificity in predicting Engel I outcomes with an SVM classifier.…”
Section: Management Of Epilepsymentioning
confidence: 99%